STUDI POLA PENGELOLAAN LIMBAH PADAT BAHAN BERBAHAYA DAN BERACUN (B3) PUSKESMAS DI KABUPATEN KAPUAS (KECAMATAN SELAT, KAPUAS HILIR, KAPUAS TIMUR, KAPUAS BARAT, KAPUAS MURUNG, PULAU PETAK DAN BASARANG) - Maria, Linda; Firmansyah, Muhammad; Mizwar, Andi; mahyudin, Rizqi Puteri; Nilawati, Indah Nirtha (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2025)
Public health center is responsible for carrying out comprehensive health services to the community in a certain work area. However, in an effort to implement it, Public health center can produce waste in the form of waste that is harmful to health. This review was conducted to analyze the management pattern of hazardous solid waste in Public health center in Kapuas Regency in accordance with the standards set out in the Peraturan Menteri Lingkungan Hidup dan Kehutanan Nomor 56 Tahun 2015. The results showed that the generation of hazardous solid waste of Public health center in Kapuas Regency has an average weight of 0.99 kg/puskesmas/day and a volume of 11.51 liters/puskesmas/day. The composition of the most waste produced by infectious waste is 40.23%. Meanwhile, the pattern of B3 solid waste management of Public health center in Kapuas Regency includes sorting, renting, collecting, moving, temporary storage and destruction, there are still many shortcomings that need to be addressed.